Changes in enteric neurone phenotype and intestinal functions in a transgenic mouse model of enteric glia disruption. Issue 5 (19th October 2005) - Aubé, A-C; Cabarrocas, J; Bauer, J; Philippe, D; Aubert, P; Doulay, F; Liblau, R; Galmiche, J P; Neunlist, M
Abstract : Aims: The influence of enteric glia on the regulation of intestinal functions is unknown. Our aim was to determine the phenotype of enteric neurones in a model of glia alterations and the putative changes in intestinal motility and permeability. Methods: Transgenic mice expressing haemagglutinin (HA) in glia were used. Glia disruption was induced by injection of activated HA specific CD8+ T cells. Control mice consisted of non-transgenic littermates injected with activated HA specific CD8+ T cells. Immunohistochemical staining for choline acetyltransferase (ChAT), substance P (SP), vasoactive intestinal peptide (VIP), and nitric oxide synthase (NOS) was performed on jejunal submucosal plexus (SMP) and myenteric plexus (MP). Neurally induced jejunal muscle activity was characterised in vitro. Gastrointestinal transit and paracellular permeability were measured using fluorescein isothiocyanate-dextran markers. Results: CD3 positive T cells infiltrates were observed in the MP of transgenic mice. In the SMP, the proportions of VIP and SP positive neurones decreased in transgenic mice compared with control mice. ChAT remained unchanged. In the MP, the proportions of ChAT and NOS positive neurones increased and decreased, respectively, in transgenic mice. In contrast, VIP and SP remained unchanged. Neurally mediated jejunal relaxation was lower in transgenic mice than in controls. This relaxation was reduced by N G -nitro-L-arginine methyl ester in control mice but not in transgenic mice. Gastrointestinal transit was delayed and intestinal permeability increased in transgenic mice compared with control mice. Conclusion: Glia disruption induces changes in the neurochemical coding of enteric neurones, which may partly be responsible for dysfunctions in intestinal motility and permeability.